Combination of laser welding with in-mould assembling into a single process - Oliveira, Nelson Duarte Mendes (2016)
In the highly competitive global automotive market, where each centime counts, the present global economic crisis has obliged companies to develop new strategies with the objective of reducing the final price of their products so as to remain competitive. To several companies the solution has been relocating their production facilities to other countries where labour cost are much lower when compared to European countries. Relocation has had particular impact within the ranks of TIER1 (supplier ranking) automotive component producing companies. This work had the objective of developing a new process capable of producing a functional automotive component in an optimised way and with a lower cost compared to existing processes. To achieve this objective intensive study was made into the concept of a manufacturing process utilising established injection moulding processes allied with the use of emergent laser welding technologies. These two processes were chosen mainly due to their capability of producing different components in a single process with a high rate of production and associated low cost.